Evaluasi Strategi Pembelajaran pada Era New Normal di SDIT Raudhatul Jannah Lubuklinggau - MUHAMMAD RIDHO NUGROHO; HADIWINARTO HADIWINARTO (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: Evaluation of Learning Strategies in the New Normal Era at SDIT Raudhatul Jannah LubuklinggauSince the Covid-19 pandemic entered Indonesia in March 2020, all learning activities in schools have been stopped, from early childhood education to higher education. This has an impact on the learning process which has stagnated for several months. SDIT Raudhatul Jannah Lubuklinggau through the LPPI (Islamic Education Development Institute) created a learning strategy during the pandemic period by continuing to apply health protocols so that the learning process was not stagnant. This study aims to evaluate the effectiveness of learning method strategies during the pandemic period designed by LPPI Raudhatul Jannah Lubuklinggau on student learning outcomes. The evaluation of the CIPP model was used with a qualitative descriptive method, conducting interviews to obtain information using questionnaires to respondents, namely the chairman of the LPPI Raudhatul Jannah. The results showed that the learning strategy in the pandemic period which was implemented in schools could work effectively, this was evident from the results of the mid-semester test of students which showed good average scores and at the time of evaluation students were able to remember and reclaim material that had been given at the time online learning.Abstract: Evaluasi Strategi Pembelajaran Pada Era New Normal di SDIT Raudhatul Jannah LubuklinggauSemenjak pandemi covid-19 masuk ke Indonesia bulan maret tahun 2020, seluruh aktivitas pembelajaran disekolah-sekolah dihentikan mulai dari tingkat pendidikan anak usia dini hingga perguruan tinggi. Hal ini berdampak pada proses pembelajaran yang mengalami stagnasi selama beberapa bulan. SDIT Raudhatul Jannah Lubuklinggau melalui LPPI (Lembaga Pengembangan Pendidikan Islam) membuat sebuah strategi pembelajaran selama masa pandemi dengan tetap menerapkan protokol kesehatan agar proses pembelajaran tidak stagnan. Penelitian ini bertujuan untuk mengevaluasi efektivitas strategi metode pembelajaran selama masa pandemi yang dirancang oleh LPPI terhadap hasil pembelajaran siswa. Evaluasi model CIPP digunakan dengan metode deskriptif kualitatif yaitu melakukan wawancara untuk memperoleh informasi menggunakan kuisioner kepada responden yaitu ketua LPPI Raudhatul Jannah. Hasil penelitian menunjukkan bahwa strategi pembelajaran di masa pandemi yang diterapkan di sekolah dapat berjalan efektif, hal ini terbukti dari hasil ujian mid semester yang menunjukkan nilai rata-rata yang baik serta pada saat evaluasi siswa mampu mengingat dan mengulang kembali materi yang pernah diberikan pada saat pembelajaran secara daring.